2007
DOI: 10.1111/j.1527-5299.2007.06408.x
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Failure in Patients With Preserved Ejection Fraction and Diastolic Dysfunction: An Underrecognized Clinical Entity

Abstract: It is well recognized that patients with severe left ventricular (LV) systolic dysfunction develop pulmonary venous hypertension or postcapillary pulmonary hypertension, which leads to an increase in pulmonary vascular resistance (PVR) and right ventricular (RV) systolic failure. It is often underrecognized, however, that patients with heart failure with preserved LV ejection fraction and diastolic dysfunction may also develop postcapillary pulmonary hypertension with elevated PVR leading to RV systolic failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Theoretically, the elevated pressure during WWI in this patient might be caused by enhanced pulmonary blood flow due to increased venous return. In combination with backward failure of the left ventricle, this could lead to an increase in pulmonary vascular resistance and worsening in RV systolic heart failure [13]. Therefore, it appears that the right ventricle failed to generate enough pressure to overcome RV afterload and thus resulted in further decompensation.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the elevated pressure during WWI in this patient might be caused by enhanced pulmonary blood flow due to increased venous return. In combination with backward failure of the left ventricle, this could lead to an increase in pulmonary vascular resistance and worsening in RV systolic heart failure [13]. Therefore, it appears that the right ventricle failed to generate enough pressure to overcome RV afterload and thus resulted in further decompensation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions can be drawn from the strong, positive association of right ventricular EF with its left-sided counterpart, not surprising because the two ventricles share common circular and spiral muscle fibre bundles, and the septal wall, a structure involved in both right ventricular ejection and filling and ventricular interdependence, ie, the transmission of forces from one to the other ventricle independent of neural, humoural or circulatory influences 35. Ventricular interdependence, however, may be overcome by contrasting pathophysiological mechanisms by which right ventricular EF may be preserved in left ventricular dysfunction36 and, vice versa, maintained systolic left ventricular function may coexist with right ventricular failure 37…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature has shown that patients with RV dysfunction or overload have worse outcomes. In patients with left heart failure or COPD, RV dysfunction or overload is associated with increased acute exacerbations and increased hospital readmissions compared with patients with normal RV function [7,21,22]. Patients with pulmonary hypertension complicated by RV dysfunction generally have a significantly poorer prognosis and decreased longevity [12,13,15].…”
Section: Discussionmentioning
confidence: 98%
“…Right ventricular dysfunction may originate from intrinsic muscle damage caused by ischemia or cardiomyopathies. More commonly, however, RV dysfunction occurs from increases in RV afterload, caused by treatable etiologies such as chronic obstructive pulmonary disease, obstructive sleep apnea, pulmonary arterial hypertension, or pulmonary hypertension secondary to left heart disease or chronic thromboemboli [7][8][9][10][11][12][13]. Detection of RV dysfunction from pulmonary hypertension is frequently underdiagnosed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation